The Effect of Low and High Glycemic Load Diet on Muscle Fatigue of Young Soccer Athletes - Safitri, Iqlima; Setyarsih, Liani; Susanto, Hardhono; Suhartono, Suhartono; Fitranti, Deny Yudi (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Muscle fatigue in adolescent soccer athletes can degrade performance during a match. A low Glycemic Load (GL) diet before exercise is believed to improve soccer athlete performance because it can decrease carbohydrate oxidation during exercise and has a lower increase in lactic acid levels than a high GL diet. The study aimed to identify the effect of low and high glycemic load diets on muscle fatigue in adolescent soccer athletes. A quasi experimental with multiple series group design was conducted in November 2019 on 22 adolescent soccer athletes aged 15-17 at the Terang Bangsa Soccer School Semarang. The low GL group was given food with GL 9.15; while the high GL group contained GL 27.29. Diets given once in 2 hours before exercise. Each group was triggered by RAST (Running based Anaerobic Sprint Test) to cause anaerobic muscle fatigue. Muscle fatigue is measured using blood lactic acid, BUN (Blood Urea Nitrogen), and fatigue index. There were no significant differences in blood glucose, lactic acid, and BUN levels between the low GL and high GL groups (p>0.05). Nonetheless, a low GL diet had a smaller increase in blood glucose levels (1.91 mg/dL vs 4.09 mg/dL) and lactic acid (4.5 mg/dL vs 4.7 mg/dL) after exercise than high BG diet. A low GL diet also has a lower fatigue index than a high GL. Keyword: glycemic load diet, muscle fatigue, lactic acid, blood urea nitrogen.